Word Square Model Used by Poster Media to Improve Primary School Student Learning Outcomes - Nurliza, Maya; Lubis, Azmil Hasan; Lubis, Silvia Sandi Wisuda (MANDAILING GLOBAL EDUKASIA, 2024)
The aim of this research is to improve student learning outcomes in Civics learning by implementing the Word Square Model Assisted by Poster Media to Improve Learning Outcomes. This type of research is PTK which includes four stages, namely: planning, implementation, observation and reflection stages carried out in three cycles, with research subjects totaling 26 students. Data collection techniques use observation instruments, questionnaires and tests. This data is analyzed using a percentage formula. The results of the research through the application of the Word Square Model Assisted by Poster Media to Improve and the Learning Outcomes of Class V Students have increased. The results of observing teacher activities in the Pre-Cycle were 45.31%, then increased in cycle I, namely 76.13%, in cycle II it increased to 88.63%, in cycle III it became 100%. Student activity in the Pre-Cycle was 43.61%, then increased in cycle I, namely 70.45%, in cycle II it increased to 93.18%, in cycle III it became 100%. Meanwhile, learning outcomes in the Pre-Cycle were 30.76%, then increased in cycle I, namely 53.86%, in cycle II it increased to 73.07%, in cycle III it became 92.30%. It can be concluded that the Word Square Model Assisted with Poster Media can increase the activity and learning outcomes of class V students at SDN 33 Banda Aceh.